2018
DOI: 10.21315/tlsr2018.29.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fatty Acid Content in Selected Freshwater Fish from Bukit Merah Reservoir, Perak, Malaysia

Abstract: One of the oldest reservoirs in Peninsular Malaysia, Bukit Merah Reservoir, is a place in which locals participate in fishing activities. Inland fisheries are important to individuals, society and the environment; whereby they generate a source of income and food security. It is essential to gauge the nutrition value of fish caught in this location as food source, especially in terms of fatty acid composition, to better demonstrate its potential towards the betterment of human health and general well-being. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This recapitulates the observations in other cyprinids and freshwater species fed VO‐based diets (Janaranjani et al., 2018; Kamarudin et al., 2012; Ren, Yu, Xu, & Tang, 2012; Tian, Lei, & Ji, 2016). Specific to the benefits of the n‐3 LC‐PUFA, the levels of muscle EPA + DHA in fish fed diets LO or LOCO were higher than diet CO and is comparable to levels reported in silver barb population elsewhere (Chedoloh, Karrila, & Pakdeechanuan, 2011; Jaya‐Ram et al., 2018). The muscle n6/n3 ratio of fish fed LO‐based diets was significantly lower than diet CO and also within the acceptable range for human health (Strobel, Jahreis, & Kuhnt, 2012).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This recapitulates the observations in other cyprinids and freshwater species fed VO‐based diets (Janaranjani et al., 2018; Kamarudin et al., 2012; Ren, Yu, Xu, & Tang, 2012; Tian, Lei, & Ji, 2016). Specific to the benefits of the n‐3 LC‐PUFA, the levels of muscle EPA + DHA in fish fed diets LO or LOCO were higher than diet CO and is comparable to levels reported in silver barb population elsewhere (Chedoloh, Karrila, & Pakdeechanuan, 2011; Jaya‐Ram et al., 2018). The muscle n6/n3 ratio of fish fed LO‐based diets was significantly lower than diet CO and also within the acceptable range for human health (Strobel, Jahreis, & Kuhnt, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…For this species, the marketable size of 300g is reached in 4–5 months. In comparison with other freshwater fish, B. gonionotus contain high levels of n‐3 LC‐PUFA (Jaya‐Ram et al., 2018). While several studies on the dietary requirements for major nutrients have been reported in silver barb, there is still a paucity of knowledge on the fatty acid nutrition (Mohanta, Mohanty, & Jena, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in growth and FCR with increasing dietary protein are typically found in carnivore fish (Gao et al, 2005). Meanwhile, tinfoil barb is omnivorous and feeding on small fish, aquatic plants and invertebrates like insects in natural habitats (Jaya‐ram et al, 2018; Mansour et al, 2016). Poorer FCR and feed intake had been reported in tilapia fry fed with a lower protein diet (Abdel‐Tawwab et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tinfoil barb ( Barbonymus schwanenfeldii ), from the family Cyprinidae, has long been an important species in the global multibillion dollar ornamental fish industry. Tinfoil barb is an omnivorous species which feeds on aquatic plants and occasionally feed on small fish and invertebrates like insects (Jaya‐ram et al, 2018). It was previously sidelined from the mainstream food fish but is now accepted as a common protein source (Jaffar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%